A novel seismic energy dissipating device, Sliding Keys on Inclined Deflecting-cantilevers (SKID): Theoretical and experimental evidence. (15th December 2022) - Zhang, Yichen; De Risi, Raffaele; Alexander, Nicholas A.
Highlights: A new dissipative frictional device is proposed based on a previous theoretical derivation. The device does not require specialised manufacturing equipment, complex production processes, or in-situ welding, indicating credible repairability. The quasi-static cyclic tests reveal that the device can exhibit stable hysteretic behaviour and satisfactory energy dissipation capabilities. Abstract: An innovative physical realisation of the previously reported conceptual frictional sliding on a sprung slope (FSSS) device is proposed in this paper. The device uses the end stiffness of cantilevers as the "sprung-slope", which generate amplitude varying normal and frictional forces along the sliding plane. This novel configuration is here termed a Sliding Keys on Inclined Deflecting-cantilevers (SKID) device. The SKID device is proposed for application with post-tensioned (PT) frames to improve lateral stiffness and energy dissipation capability without inhibiting their self-centring features. The configuration and theoretical properties of the device are presented. In particular, the reliability of using cantilever bars as a means of generating an amplitude-dependent normal force at the sliding surfaces is discussed. Then, two 1/4 scale-reduced prototypes, which have (i) negative unloading stiffness (SKID A) and (ii) positive unloading stiffness (SKID B), were designed and manufactured. Both specimens were subjected to the same quasi-static cyclic loading protocol. It was found that they exhibited stable and repeatable triangular-shaped hysteretic curves. The theoretical hysteretic load/deflection envelopes are compared with test specimen results, verifying a satisfactory consistency between the theoretical and physical SKID device.